From interfaith dialogue to theological discourse: Al-Faruqi's legacy in interfaith engagements - Kamaruzaman, Kamar Oniah (I.B. Tauris & Co Ltd, 2012)
This piece is on al-Faruqi's contributions and involvement in Interfaith dialogues and cross-civilizational engagements. It traces the making of al-Faruqi as an eminent scholar of Comparative Relgion and his scholarship in this field, Attention is also given to his methodology in Religionswissenschaft, in particular his concept of meta-religion and Phenomenology of Religion.